Ação da curcumina e morina em leveduras do Complexo Cryptococcus neoformans - Freitas, Vivianny Aparecida Queiroz (2017)
Cryptococcosis is a fungal disease caused by yeasts belonging to the complex Cryptococus neoformans. The antifungal arsenal available for the treatment of this disease is still restricted and is related to the high toxicity and side effects of some drugs, causing great harm to the patients. In this context, it is necessary to discover new bioactives to quell the infections and reduce the adverse effects. The plants have rich source of secondary bioactive metabolites such as tannins, terpenoids, saponins, alkaloids, flavonoids and other compounds, registered with expressive antimicrobial properties. Therefore, the research of natural compounds and derivatives of natural products has been relevant in recent years, due to their relevance in the discovery of new drugs, in addition to which the association of drugs or compounds with different mechanisms of action has been used as an alternative in conventional therapy. We evaluated the mechanisms of action and antifungal effect of natural compounds, curcumin and morin, on Cryptococcus neoformans and Cryptococcus gattii isolates. The antifungal activity was determined across the minimum inhibitory concentration (MIC) and minimum fungicide (MFC). Polyphenols showed MICs ranging from 2 to 256 μg/mL. The compounds showed a synergistic interaction in 30% (6/20) and 15% (3/20) of the isolates when dealing with morin and curcumin, respectively, associated with fluconazole. In the interaction with amphotericin B morin presented synergism in 70% (14/20) of the isolates. Both compounds did not exhibit antagonism in any of the combinations. Changes in fungal cell morphology were observed, and in contact with red blood cells, presented low toxicity. The mechanisms of action revealed that both polyphenols act on the membrane of the fungal cell, inhibiting the synthesis of ergosterol and causing damage to it. These results demonstrate the potential of the compounds as natural bioactives, with great impact on the discovery of new drugs and their efficacy to be used in the treatment of fungal infections.